A description of the established modifiable risk factors for hypertension amongst adult Batwsana in the Gaborone District - Kuhlmann, Janet (My University, 2014)
Hypertension is a m ajor disease in the black population o f Sub-Saharan Africa and the United States o f America. It is one o f the m ajor risks for cardiovascular mortality and morbidity w hich contributes to disability and increased health care costs. Studies have revealed that socio- economic changes, influenced by Western lifestyles in developing countries, have to a large extent resulted in this health problem. The researcher set out to conduct a survey to describe the established modifiable risk factors for hypertension among Batswana in the Gaborone District. The modifiable risk factors for hypertension consist o f lugh salt intake, alcohol consumption, high blood cholesterol, high fat consumption, obesity, physical inactivity, diabetes and stress. The setting was in a Prim ary Health Care clinic. The sample consisted o f 158 adults who were 18 years and above and who had been diagnosed with hypertension and seen during a follow up over a period o f two months. A face to face structured interview plus record review was used to collect data on biographical factors, socio economic factors, lifestyle factors and medical history. A finger pin prick to obtain a blood sample for cholesterol and glucose was done. Weight and height were m easured to w ork out body mass index. Descriptive statistics were used to present the interpretation o f data which was coded and analysed by com puter using Statistical Package for Social Sciences.